2012
DOI: 10.1128/cvi.05630-11
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Analysis of the Humoral Immune Response to Moraxella catarrhalis and Streptococcus pneumoniae Surface Antigens in Children Suffering from Recurrent Acute Otitis Media and Chronic Otitis Media with Effusion

Abstract: ABSTRACTA prospective clinical cohort study was established to investigate the humoral immune response in middle ear fluids (MEF) and serum against bacterial surface proteins in children suffering from recurrent acute otitis media (rAOM) and chronic otitis media with effusion (COME), using Luminex xMAP technology. The association between the humoral immune response and the presence ofMoraxella catarrhalisand<… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
8
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 40 publications
2
8
1
Order By: Relevance
“…Further studies are proposed to disclose the immune features of OMP CD contributing to these discrepancies. In another study, Verhaegh and co-workers did not find a correlation between the serum and MEF antibody levels to ten recombinant Mcat proteins or Mcat NP colonization and AOM events in children under 5 years old during recurrent AOM and chronic otitis media with effusion [10]. Our observations and those of others indicate that there is a complicated interplay between the host antibody immune response and Mcat acute infections.…”
Section: Discussionsupporting
confidence: 41%
“…Further studies are proposed to disclose the immune features of OMP CD contributing to these discrepancies. In another study, Verhaegh and co-workers did not find a correlation between the serum and MEF antibody levels to ten recombinant Mcat proteins or Mcat NP colonization and AOM events in children under 5 years old during recurrent AOM and chronic otitis media with effusion [10]. Our observations and those of others indicate that there is a complicated interplay between the host antibody immune response and Mcat acute infections.…”
Section: Discussionsupporting
confidence: 41%
“…Furthermore, a recent report indicates a nonsignificant increase in MEF IgA levels against the pneumococcal IgA-1 protease protein in S. pneumoniae-negative/COME-positive children, which may indicate a role in improving the binding of IgA to improve bacterial clearance. This study also reported evidence of a positive correlation between antigen-specific serum and MEE IgG levels for both M. catarrhalis and S. pneumoniae antibodies, which suggests that the antibody response in the middle ear is derived from both the systemic circulation and local mucosal tissue in the middle ear (Verhaegh et al, 2012).…”
Section: Secretory Immunoglobulin a In The Middle Earsupporting
confidence: 61%
“…In this report we describe the development and careful laboratory validation of a bead based multiplex immunoassay for the simultaneous evaluation of the presence of serum antibodies against S. pneumoniae, H. influenzae, and M. catarrhalis using protein antigens, including several vaccine candidates. Although the use of multiplex assays using pneumococcal proteins has been reported previously (Lebon et al, 2011;Prevaes et al, 2012;Verhaegh et al, 2012), the description of such assays has only been partially published (Shoma et al, 2011), and no data on aspects such as the specificity and comparability with the other assays is available so far. Additionally, this is the first study reporting the validation of a multiplex assay for this specific set of pathogens causing respiratory tract disease, including the information on the possible interference of heterologous inhibition (Prevaes et al, 2012;Verhaegh et al, 2012).…”
Section: Discussionmentioning
confidence: 99%